Ceramics From Ti-Extraction Blast Furnace Slag and Their Crystalline Phase, Microstructure, and Photocatalytic Performance - You, Hao; Sun, Hongjuan; Li, Yao; Peng, Tongjiang (Frontiers in Materials, 2021)
To solve the environmental problems caused by the deposition of Ti-extraction blast furnace slag (EBFS) and to develop the functionality of the slag ceramics, photocatalytic EBFS ceramics were prepared via powder sintering at different temperatures. The phase composition dramatically changed in ceramics sintered at 1000~1150°C but remained constant in samples treated at 1150~1200°C, just revealing the variations in the relative content of each phase. The photocatalytic performance of samples was assessed through the catalytic degradation of Rhodamine B (RhB). Furthermore, it was shown to strongly depend on the relative Fe-bearing diopside content, achieving a maximum in EBFS-1180 ceramic. In this ceramic, the Fe-bearing diopside was found to degrade up to 77% of RhB under UV light irradiation at pH = 2 and its acid corrosion ratio after 24 h was only 0.03%, indicating that EBFS-1180 ceramic had the ability to degrade pollutants in an acidic environment.